2015
DOI: 10.1080/10286020.2015.1121999
|View full text |Cite
|
Sign up to set email alerts
|

Triterpene saponins with α-glucosidase inhibition and cytotoxic activity from the leaves of Schefflera sessiliflora

Abstract: From the leaves of Schefflera sessiliflora De P. V., two new triterpene saponins including one oleanane-type saponin, named scheffleraside C (1) and one lupane-type saponin scheffleraside D (2), together with six known triterpene saponins (3-8), were isolated by various chromatography methods. Among them, 3 was found for the first time from natural sources, while 6-8 were isolated for the first time from the genus Schefflera. Their structures were elucidated by IR, UV, HR-ESI-MS, NMR 1D and 2D experiments, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 16 publications
2
3
0
Order By: Relevance
“…The quinoa husk extracts showed a lower IC 50 value of 32.62 mg/mL compared to that of acarbose (64.71 mg/mL), suggesting a stronger inhibition on α-glucosidase (p < 0.05). Our finding is consistent with the previous reports of the strong effect of triterpenoid saponins and flavonoids in inhibiting the activity of α-glucosidase [50,51]. Moreover, studies also suggest the functions of key groups in the structure of flavonoids and triterpenoid saponins in their α-glucosidase inhibiting activity, such as the number and position of hydroxyl groups and the carbonyl group in flavonoids [52] and the position of sugar moieties in the aglycon in triterpenoid saponins [53].…”
Section: Identification Of Chemical Constituents In Quinoa Husk Extractssupporting
confidence: 92%
“…The quinoa husk extracts showed a lower IC 50 value of 32.62 mg/mL compared to that of acarbose (64.71 mg/mL), suggesting a stronger inhibition on α-glucosidase (p < 0.05). Our finding is consistent with the previous reports of the strong effect of triterpenoid saponins and flavonoids in inhibiting the activity of α-glucosidase [50,51]. Moreover, studies also suggest the functions of key groups in the structure of flavonoids and triterpenoid saponins in their α-glucosidase inhibiting activity, such as the number and position of hydroxyl groups and the carbonyl group in flavonoids [52] and the position of sugar moieties in the aglycon in triterpenoid saponins [53].…”
Section: Identification Of Chemical Constituents In Quinoa Husk Extractssupporting
confidence: 92%
“…Several triterpenoid saponins were isolated from Gypsophila oldhamiana roots and the results shows that all active compounds exhibited better α-GIA than acarbose with IC50s between 15.2 and 98.2 µM, whereas the IC50 of acarbose was 388.0 µM [114] . Furthermore, in 2015, a study by Nguyena et al revealed that triterpenoid saponins isolated from Schefflera sessiliflora leaves showed greater α-GIA (IC50 = 5.99 -76.58 µM) than acarbose (IC50 = 214.5 µM) [115] , and this may support our hypothesis of saponin content are compounds responsible for α-GIA from the precipitate extract.…”
Section: α-Glucosidase Inhibitory Activitysupporting
confidence: 80%
“…Even though there are reports on terpenoid saponins as α-glucosidase and α-amylase inhibitors, as far as we know, this is the first report of a lanosterol saponin with α-amylase inhibitory activity.…”
Section: Resultsmentioning
confidence: 85%